Expectations from preceding prosody influence segmentation in online sentence processing - Brown, Meredith (2011)
Previous work examining prosodic cues in online spoken-word recognition has focused primarily on local cues to word identity. However, recent studies have suggested that utterance-level prosodic patterns can also influence the interpretation of subsequent sequences of lexically ambiguous syllables (Dilley, Mattys, & Vinke, Journal of Memory and Language, 63:274–294, 2010; Dilley & McAuley, Journal of Memory and Language, 59:294–311, 2008). To test the hypothesis that these distal prosody effects are based on expectations about the organization of upcoming material, we conducted a visual-world experiment. We examined fixations to competing alternatives such as pan and panda upon hearing the target word panda in utterances in which the acoustic properties of the preceding sentence material had been manipulated. The proportions of fixations to the monosyllabic competitor were higher beginning 200 ms after target word onset when the preceding prosody supported a prosodic constituent boundary following pan-, rather than following panda. These findings support the hypothesis that expectations based on perceived prosodic patterns in the distal context influence lexical segmentation and word recognition.